Barangay Payatas Quezon City Drug Prevention Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Drugs are a kind of medication that have a wide range of therapeutic applications. Drugs canbe classified as illegal in the modern world since they are frequently abused for excessiveconsumption, which generates addiction. Researchers aimed to address this issue,particularly in Barangay Payatas, Quezon City, Philippines and provided the community withthe finest preventative program to increase residents' and adolescents' knowledge. Theresearcher is of the opinion that a nation will be improved by a cohesive community and law-abiding citizens. The purpose of this study is to identify the prevalent issues that BarangayPayatas in Quezon City faces. As researchers, we hope to offer a remedy for the issuesrelated to illegal drugs and drug users. Last but not least, researchers will be aware of theaspects that could have an impact on the nation and community on illegal substances.This chapter presents information from twenty (20) Barangay authorities of Barangay Payatasin Quezon City. And fifty (50) residents who took part in the survey as responders. Inaccordance with the given research topics, it also provides an analysis and interpretation ofthe data that has been acquired.This chapter summarized the study's findings, output, conclusion, and recommendation.Studying the Barangay Payatas Quezon City Drug Prevention Program. Barangay Payatas,Quezon City residents responded. Seventy male and female respondents were surveyed.This study found that most responders are single women aged 17–22 and 23 and older. Thisstudy recommended adding drug rehabilitation centers to each barangay and supervising thewatch list for drug surrenderers and PWUDS.
Keywords: Criminology